Beyond Surface Beauty: Exploring the Intricate Histopathological Finding in Intrinsic Dentin Discoloration - De Sriparna; Pallavi Vashisth; N. Sathyajith Naik; Rasleen Dua (Indian Journal of Dental Sciences, 2024)
Dental stains are pigmented deposits that can be intrinsic or extrinsic in origin and are seen on the surface of the teeth. Discoloration of teeth can be due to developmental defects, traumatic injuries, or the intake of several medications. Extrinsic stains create discoloration outside the tooth surface and lay on the surface or in the acquired pellicle, whereas stains within dentin or intrinsic discoloration sometimes come from pulpal or systemic origin. To plan a specific treatment approach and its associated result, it is important to identify the etiologic cause that is creating the stain, in an attempt to provide esthetic treatment for the same. This case report describes the successful management of intrinsic staining of anterior teeth in a 10-year-old girl. The treatment plan included esthetic rehabilitation using composite veneer. The fluoride-releasing composite used provided an acceptable color match and exceptional handling properties and was relatively easy to maintain with its antiplaque effect. This case also represents a unique histopathological finding from ground sections of a retained extracted deciduous tooth.